Excitation and relaxation dynamics in ultrafast laser irradiated optical glasses. (12th December 2016) - Mauclair, C.; Mermillod-Blondin, A.; Mishchik, K.; Bonse, J.; Rosenfeld, A.; Colombier, J. P.; Stoian, R.
Abstract : We discuss the dynamics of ultrashort pulsed laser excitation in bulk optical silica-based glasses (fused silica and borosilicate BK7) well-above the permanent modification threshold. We indicate subsequent structural and thermomechanical energy relaxation paths that translate into positive and negative refractive index changes, compression and rarefaction zones. If fast electronic decay occurs at low excitation levels in fused silica via self-trapping of excitons, for carrier densities in the vicinity of the critical value at the incident wavelength, persistent long-living absorptive states indicate the achievement of low viscosity matter states manifesting pressure relaxation, rarefaction, void opening and compaction in the neighboring domains. An intermediate ps-long excited carrier dynamics is observed for BK7 in the range corresponding to structural expansion and rarefaction. The amount of excitation and the strength of the subsequent hydrodynamic evolution is critically dependent on the pulse time envelope, indicative of potential optimization schemes.